Pengaruh Strategi Pemasaran Dalam Meningkatkan Nasabah Bank Syariah Studi Kasus Desa Payageli - Jamila, Khaidar Rahmaini; Rizqiyah, Anisah; Maysarah, Maysarah; Jewina, Haliza (Universitas Islam Negeri Sumatera Utara, 2023)
Payageli village hamlet 1 is a village in Deli Serdang with a majority Muslim community. The people in the village know about the existence of sharia banks but there is a lack of socialization carried out by sharia banks so that the village people are comfortable with using conventional banks so they are no longer interested in using sharia banks. This research aims to analyze the influence of marketing strategies in increasing sharia bank customers in Payageli village. This research uses quantitative methods and uses a descriptive approach. Data collection in this research used purposive sampling using interviews and distributing questionnaires. Data analysis was carried out with the help of the SPSS version 27 application. The conclusion of this research is that the calculated t value of Marketing Strategy is 10.043, there is a significant level of 0.00, this is because tcount is 10.043>ttable 1.665, therefore it can be concluded that h2 is accepted and h0 is rejected which is It can be stated that marketing strategies have a positive effect on increasing customers